PEMBERDAYAAN MASYARAKAT DALAM MEWUJUDKAN EFEKTIVITAS PENYELENGGARAAN PENDIDIKAN - Dwi Deswary (Perspektif Ilmu Pendidikan, 2007)
Nonformal education plays equal roles in educating people. However, in practice more attention and efforts are given to the formal education. This article discusses how to strengthen the role of non-formal education by enhancing communities’ participation. This could be successfully done if the personnel of nonformal institutions are dedicated, honest, innovative, dilligent, and intelligent. The empowerement of communities to support the non-formal education activities will improve the effectiveness and the efficiency of non-formal education programs.